Pengembangan Prototipe Piranti Lunak Sistem Informasi Manajemen Kegiatan Perekayasa Dengan Microsoft Excel - Ivransa Zuhdi Pane (Universitas Multimedia Nusantara, 2014)
Management of engineering activities based on information systems is expected to increase Engineer’s perfomances in executing the daily tasks. The software of such management information system should be built on the platform which is easy to use and adaptable to the dynamics of engineering activity management in the future. Software engineering, consisting of analysis, design and implementation, was carried out to realize a prototype which is ready to be applied in the further development stages. Index Terms - engineering activity, Engineering, information system, software engineering.